Ancestral smoking and developmental outcomes: a review of publications from a population birth cohort. Issue 3 (25th June 2021) - Golding, Jean; Pembrey, Marcus; Iles-Caven, Yasmin; Watkins, Sarah; Suderman, Matthew; Northstone, Kate
Abstract: The adverse effects on the child of maternal smoking in pregnancy is well-recognized, but little research has been carried out on the possible non-genetic effects of ancestral smoking prior to the pregnancy including parental initiation of cigarette smoking in their own childhoods or a grandmother smoking during pregnancy. Here, we summarize the studies that have been published mainly using data from the Avon Longitudinal Study of Parents and Children. We demonstrate evidence that ancestral smoking prior to or during pregnancy can often be beneficial for offspring health and both ancestor- and sex-specific. More specifically, we report evidence of (i) adverse effects of the father starting to smoke pre-puberty on his son's development; (ii) beneficial effects on the grandson if his maternal grandmother had smoked in pregnancy; and (iii) mainly adverse effects on the granddaughter when the paternal grandmother had smoked in pregnancy. The ancestor- and sex-specificity of these results are consistent with earlier studies reporting associations of health and mortality with ancestral food supply in their parents' and grandparents' pre-pubertal childhoods. Abstract : Review of published ALSPAC studies demonstrate ancestral smoking prior to pregnancy can be beneficial or detrimental for offspring health and development and often both ancestor- and sex-specific.